HIV acquisition is associated with increased antimicrobial peptides and reduced HIV neutralizing IgA in the foreskin prepuce of uncircumcised men. - Taha Hirbod (Public Library of Science (PLoS), 2014)
Background The foreskin is the site of most HIV acquisition in uncircumcised heterosexual men. Although HIV-exposed, seronegative (HESN) uncircumcised men demonstrate HIV-neutralizing IgA and increased antimicrobial peptides (AMPs) in the foreskin prepuce, no prospective studies have examined the mucosal immune correlates of HIV acquisition. Methods To assess the association of foreskin immune parameters with HIV acquisition, antimicrobial peptides and IgA with the capacity to neutralize a primary clade C HIV strain were quantified by blinded investigators, using sub-preputial swabs collected longitudinally during a randomized trial of male circumcision for HIV prevention in Rakai, Uganda. Results Participants were 99 men who acquired HIV (cases) and 109 randomly selected controls who remained HIV seronegative. At enrollment, 44.4% of cases vs. 69.7% of controls demonstrated IgA neutralization (adjusted OR = 0.31; 95% CI, 0.16-0.61). IgA neutralization was detected in 38.7% of cases and 70.7% of controls at the last seronegative case visit prior to HIV acquisition and the comparable control visit (adjusted OR 0.21; 95% CI, 0.11-0.39). Levels of the α-defensins and secretory leukocyte protease inhibitor (SLPI) were over ten-fold higher in the foreskin prepuce of cases who acquired HIV, both at enrollment (mean 4.43 vs. 3.03 and 5.98 vs. 4.61 log(n) pg/mL, P = 0.005 and 0.009, respectively), and at the last seronegative visit (mean 4.81 vs. 3.15 and 6.46 vs. 5.20 log(n) pg/mL, P = 0.0002 and 0.013). Conclusions This prospective, blinded analysis is the first to assess the immune correlates of HIV acquisition in the foreskin. HIV-neutralizing IgA, previously associated with the HESN phenotype, was a biomarker of HIV protection, but other HESN associations correlated with increased HIV acquisition. This emphasizes the importance of prospective epidemiological studies or in vitro tissue studies to define the impact of mucosal parameters on HIV risk.